Work-family enrichment: it’s mediating role in the relationships between dispositional factors and job satisfaction - Ng, Swee Fung; Ahmad, Aminah; Omar, Zoharah (Human Resource Management Academic Research Society, 2015)
The growing interest in understanding the interface of work and family roles, in particular work-family enrichment, and its antecedents and outcomes, has stimulated the development of a mediation model. The mediation model developed includes dispositional factors (optimism, self-efficacy) as antecedents, job satisfaction as the outcome, and work-family enrichment as the mediator. This present model is developed based on the conservation of resources theory (Hobfoll, 1989), the model of work-family enrichment (Greenhaus & Powell, 2006) and the social exchange theory (Blau, 1964). This model presents the mechanism of how dispositional factors could influence job satisfaction among employees through work-family enrichment.